Study of Health Care Services at Tertiary Care Setting and Patient Satisfaction - Fatima Kanwal, Komal Shahid Abbasi, Huda Khalid Sufi, Khawaja Muhammad Junaid, Shariq Ali Khan, Adeel Tuasene (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction:The care of the patients is the main purpose of the hospitals. The performance of the hospital can best be measured by assessing the satisfaction of the patients. Patients’ satisfaction with services of the healthchieflygoverns their compliance with the treatment, and thereforedonates to optimistic effect on health. The satisfaction of the patients is related to the outcomes of health care and is related directly to the use of health care. The aim of the study is to evaluate the satisfaction level of patients and use of health services of outpatients admitted to thetertiary care hospital. Methods: A cross-sectional study of outpatients (18 to 85 years old) admitted to different departments of Lahore General Hospital, Lahorefor six-months duration from June 2021 to November 2021was conducted. A systematic random sampling method was applied to select the participants. 160 total outpatients were recruited for the study. A partially structured, pre-tested, user-designed questionnaire was developed to assess patient satisfaction with healthcare services. Results:160 patients from the clinic were included in the study. 34.4% of outpatients are 30-45 years of age. 30% of the respondents were illiterate. 6.9% were graduates indicating a higher level of education. Most of the respondents (90.6%) are married. In the profession, 37.5% belong to the unskilled group. It can be seen that the percentage of rural areas is quite high. In access to hospital, 20.39% travelled less than 2 km to reach the hospital, and 35% travelled between 6 km and 10 km to access health services. 75% of patients travelled by bus to go to the health service (Table 2). All patients were asked why they chose this hospital. Good treatment (52.5%), easy access (53.8%) and lower cost / free service (47.65%) were the main reasons indicated by the respondents. Other reasons, such as ambulance service, drug supply, scientific research, and the availability of doctors, were not taken into account, and the satisfaction with the public hospital was below 20% Conclusion: Patients are satisfied generally with the facilities of hospital. Hospital management should always pay attention to the patient’s concerns about various deficiencies in order to improve the service provided to the satisfaction of patients.